A Checklist of Stony Corals from the Malitbog Area of Western Sogod Bay, Southern Leyte, Philippines - Fenner, Douglas; Walker, Ryan; Raines, Peter (Silliman Journal, 2022)
The coral reefs of the Philippines are some of the most bliodiverse in the world. This study consisted of a rapid diversity assessment of the coral communities in Sogod Bay, southern Leyte. A total of 276 species and 72 genera of stony corals were found across 7 dive sites, averaging 110 species per site. This number represents approximately 59% of all coral species reported for the Philippines. Four species were found that are considered to be uncommon to rare, and a total of 5 species found have not been reported to occur in the Philippines in previous published literature. The high coral diversity of Sogod Bay suggests that the reefs of the area are of high conservation importance.